Faktor Faktor yang Mempengaruhi Kebugaran Calon Jemaah Haji Kota Palembang Tahun 2019 - Y Yusri; M Zulkarnain; Rico Januar Sitorus (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2020)
Background: Physical fitness status of hajj pylgrime candidate in Palembang in 2018 has low and very low category. The category is still relative high and the score is 23.3 %. The research objective is to analyze the factors that influence physical fitness of hajj pylgrime candidate in Palembang City.Methods: An analitycal study was conducted with a cross sectional design on Juli - Agustus 2019. The study population is 2444 hajj pylgrims candidate of Palembang City in 2019 who have done checking physical health and physical fitness test by eight Puskesmas of Hajj Checking Health. 313 samples choosen by means of proportional random sampling. Data collection instrument was a data calecting paper that contains research variables. Tthe data taken from health checking form and physical fitness test form which is available in the puskesmas. The data were analyzed using chi-square and logistic regression.Result: 107 respondens ( 34,2% ) have physical fitness status is not fit. Statistical test showed that age ≥ 60 years variable (p=0,000. PR = 3,601), gender variable (p=0,024. PR=2,113), Hypertension (p=0,001. PR=2,565), waist circumstance variable (p=0,003. PR=3,173), Body Mass Indeks (BMI) variable (p=0,000. PR=3.567) and Diabetes Mellitus (DM) variable (p=0,042. PR=2,360) influence the physical fitness. Age variable is the variable that has the greatest influence the physical fitness of hajj pylgrime candidates. The researcher suggests that physical activity excirse by regularly and rotine in waiting periode will increase physical fitness.Conclusion: There are relationship age, gender, Hipertension, waist circumstance, Body Mass Indeks (BMI) and Diabetes Mellitus with physical fitness status.